A survey on E- payment systems - Shayma Shakeeb Mohammed; Yaseen Hikmat Ismael (المجلة العراقية للعلوم الاحصائية, 2024)
significant impact on global trade in the modern era. This has given rise to a new industry known as "electronic commerce," or "E-commerce," which is the use of smart devices and the internet for the exchange and display of goods and products. The need for a means of transferring money between people and businesses globally led to the creation of the so-called electronic payment, which is the foundation of electronic commerce and involves using computers and other smart devices to transfer money between the bank accounts of the relevant parties. This paper reviewed the most important electronic payment methods currently available and the security features of each method, as the adoption of any method depends on the availability of service by the responsible authorities in a particular region and the living level of that region. But, in general, mobile wallet applications that use NFC technology are considered one of the most adopted methods worldwide due to their ease of use and the availability of NFC service in most modern smartphones.